Distressed debt trading : understanding international and domestic secondary markets - Denniston, Karol K. (London : Euromoney Books, 2000)
This is the first book to analyse international distressed debt and the developing standards of practice and documentation which accompany the different trading platforms worldwide. The insolvency issue which underlies this trading is examined, with regard to the US and UK markets.
Includes bibliographical references (p. 275-277).
oif 27/08/15
Loan
Keywords: Debts, External; Investments, Foreign; Secondary markets; Debt relief; Bankruptcy